Computational analysis of thermal energy distribution of electromagnetic Casson nanofluid across stretched sheet: Shape factor effectiveness of solid-particles - Hussain S.M.; Jamshed W.; Kumar V.; Kumar V.; Nisar K.S.; Eid M.R.; Safdar R.; S. S.U.D.; Abdel-Aty A.-H.; Yahia I.S. (My University, 2025)
The present analysis focuses on using Casson nanofluid in a porous solar collector flow on an infinite surface. Nanofluid flow is altered on stretched surface induction. Nonlinear ordinary differential equations (ODEs) are derived and impaired by reducing boundary conditions to suited similarity transformation. Set of ODEs were solved approximately using the Keller box technique. Results were analyzed and elaborated for Copper-engine oil (Cu-EO) nanofluid and Ferro oxide-engine oil Fe3O4-EO nanofluid as well. Skin friction coefficient increased significantly while the Nusselt number decreased with an induced magnetic parameter. Moreover, the net system entropy was higher along with the flow velocity and the non-dimensional Brinkman number. The study revealed a better collecting of heat with Casson-nanofluid. Heat transfer rate is a crucial parameter of Cu/Fe3O4-EO as a working fluid. Net thermal efficiency enhancement of Cu-EO over Fe3O4-EO is found to have a minimum of 2.7% and an optimum of 18.5%. © 2021 The Authors